Current Correction Techniques of Food Selectivity in Children with Autism Spectrum Disorders (ASD) - Tuguleva V. (Moscow State University of Psychology and Education, 2018)
According to various reports, eating disorders in children with ASD can occur in 70-90% of cases. The article provides review of studies on the problems of food selectivity in children with autism. Presented results of the author's study of food selectivity correction techniques in children with autism spectrum disorders, conducted from October 2015 to May 2017. It was revealed that parents of children with ASD have certain types of behavior that are different from the behavior of parents with neurotypical children. It has also been determined that early aged children with ASD have specific features of eating behavior, including various degrees food selectivity, as well as functioning features of the sensory systems and the gastrointestinal tract.